Influence of combinatorial annealing and plastic deformation treatments on the intrinsic properties of Cu46Zr46Al8 bulk metallic glass. (December 2020) - Rezvan, A.; Sarac, B.; Soprunyuk, V.; Kim, J.T.; Song, K.K.; Li, C.J.; Schranz, W.; Eckert, J.
Abstract: In this paper, the effect of severe plastic deformation (SPD) induced by high-pressure torsion (HPT) and isothermal heat treatment (HT) below the glass transition on the structure-property relationships of Cu46 Zr46 Al8 bulk metallic glass (BMG) is assessed separately and alternately in reference to the as-cast state. Pronounced modifications are confirmed by X-ray diffraction, differential scanning calorimetry, dynamic mechanical analysis (DMA), dilatometry analysis, and scanning electron microscopy. Diffusion-controlled crystallization is achieved via HT with optimized parameters, and HPT is used afterwards to disperse crystalline phases relatively homogenous throughout the matrix. The dispersion of the second phase improves the thermomechanical stability around the glass transition temperature, as confirmed by DMA. Compared to a single HT process, a sequential combination of HT + HPT leads to a glass showing a linear hardness profile with values higher than the as-cast state. This study provides insights into possible processing routes for enhancing the mechanical and/or thermal properties of CuZr-based BMGs, which can also be used to tailor new design routes for other BMG systems. Highlights: Two-stage treatments of annealing and high-pressure torsion are promising processing routes to enhance the properties of CuZr-based BMGs. Controlled crystallization is achievedby heat treatment, and HPT is used afterwards to disperse crystalline phases homogeneouslyin the matrix. HT + HPT leads to a glass exhibiting even hardness profile with hardness values higher than the as-cast. HT + HPT improves the thermomechanical stability around the glass transition temperatures according to DMA.